Evaluation of the well-being of family caregivers of adults with malignant neoplasm in the home environment - William Tiago Oliveira; Catarina Aparecida Sales; Carlos Alexandre Molena Fernandes; Maria do Carmo Lourenço Haddad (Universidade Federal de Goias, 2015)
The aim of this study was to analyze the well-being of family caregivers of adults with malignant neoplasms in the home environment by means of the Avaliação de Bem-Estar Global (a validated version of the General Comfort Questionnaire for Brazilian Portuguese). A cross-sectional study was developed in Maringá, in the state of Paraná, comprising 96 caregivers. Data were collected between July 2011 and February 2012. Results were analyzed using descriptive statistics. The presence of spirituality and the benefits of a network offering support for care provision are factors that contributed to promoting well-being. Family concerns and physical and emotional discomfort of the patient were the items that had the lowest scores. When comparing the results with a study developed in a hospital environment, we concluded that the scenario has little effect on well-being. However, some items suggest care provided at home has a greater impact on the well-being of caregivers.